Measuring device for three-dimensional coordinate values of complex bent pipe - ZHANG LONG; ZHANG HAO; LIU YANGYUAN; WEN PEITIAN; WANG LIANG; YANG KE (2021)
The invention relates to a measuring device for three-dimensional coordinate values of a complex bent pipe. The measuring device comprises a guide groove, a movable base, a fastening knob, a universal pin shaft and a laser range finder. The transverse guide grooves and the longitudinal guide grooves are connected and then fixed to the workbench through bolts. The horizontal moving base is installed in the transverse guide groove and the longitudinal guide groove, and after the horizontal moving base and the vertical moving base move to the corresponding positions, the first fastening knob and the second fastening knob fasten the horizontal moving base and the vertical moving base respectively. The bent pipe is inserted into the universal pin shaft, the first laser range finder sleeving the bent pipe measures the Z coordinate of any position of the bent pipe, the second laser range finder measures the X and Y coordinates of the position, and the measured three-dimensional coordinate value of any point of the b